AB0202 Galectin-9 is a Robust Biomarker for Disease Activity in Juvenile Dermatomyositis and Acts as a T Cell Activator. (9th June 2015) - Bellutti Enders, F.; Wienke, J.; de Jager, W.; Wedderburn, L.; Nistala, K.; Pilkington, C.; Prakken, B.; van Royen-Kerkhof, A.; van Wijk, F.
Abstract : Background: Juvenile dermatomyositis (JDM) is a rare, but severe chronic systemic autoimmune disease in children, characterized by muscle weakness and a typical skin rash. Clinical evaluation of disease activity remains challenging. Recently, we identified a protein that highly correlates with disease activity in a Dutch JDM cohort: galectin-9 (gal-9). The immunobiological role of gal-9 in autoimmune diseases is still controversial. On the one hand it is known for its immunosuppressive effects by inducing apoptosis in T-helper (Th) 1 and Th17 cells and activating regulatory T cells, on the other hand it has been implicated in T cell activation and Th1 skewing. Objectives: To validate the potential of gal-9 as a biomarker in JDM and investigate its immunobiological effects on T cell skewing and activation. Methods: Gal-9 was measured in patient's serum of an independent JDM cohort by multiplex immunoassay. For functional experiments, naive CD4 T cells were isolated and stimulated with different concentrations of gal-9, plus anti-CD3 and antigen presenting cells. To test specificity, a gal-9 blocking agent (TIM-3 fusion protein) as well as a control from the galectin family (galectin-8) were included. Flow cytometric analysis of proliferation and T cell activation markers was performed on day 3 and 5 of culture. Cytokines TNFα, IFNγ, IL-13, IL-17 and IL-10 were measured in the culture supernatants of days 3, 5 and 7 by multiplex immunoassay. Results: Measurement of gal-9 in serum confirmed its high discriminative value for active disease versus remission ( P =.0001; AUC 0.894; OR 9.17) even under medication, as well as a strong correlation with the clinical disease activity scores CMAS and Physician's Global VAS. On a functional level, the presence of gal-9 induced a slight but significant increase in naive CD4 T cell proliferation after 3 days of culture. The T cell activation markers CD25, CD69 and TIM-3 showed the same pattern. Gal-9 also increased production of IFNγ, TNFα and IL-10, mainly at day 7. These effects were not seen in the control conditions. Conclusions: We confirmed the potential use of a very robust biomarker, galectin-9, that highly correlates with disease activity in juvenile dermatomyositis. Introduction of this biomarker into clinical practice will help to personalize treatment. Functionally, we found that gal-9 is a T cell activator, causing increased proliferation, cytokine production and expression of T cell activation markers. The high levels of circulating gal-9 in JDM patients may therefore contribute to the immunopathogenesis of JDM. References: Bellutti Enders et al. Correlation of CXCL10, TNFRII, and Galectin-9 With Disease Activity in Juvenile Dermatomyositis. Arthritis Rheumatol. 2014 Aug;66(8):2281-9. Disclosure of Interest: None declared